Growth Performance of Japanese quail (Coturnix coturnix japonica) reared on deep litter and cages in the hot humid tropics of Southern Bénin Republic - Alindekon, Serge; Abu, Okhiomah Ahmed; Babayemi, Jacob Olaniyi; Agblo, Paul; Adjovi-boco, Yvonne Mehouede (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2018)
The performance of male and female quails reared separately in cages and on deep litter was investigated. One hundred and eighty 3-week old quails managed for five weeks. There were three replicates per treatment with stocking densities of 120cm2/bird in cage and 180cm2/bird on deep litter and sex as a block factor. Data on weekly body weight, weight change, daily feed and water intakes, feed: gain, carcass yield and costs of production were analysed. Daily water consumed by quails between the housing systems (62.76±11.21mL/d on deep litter vs. 66.96±12.18mL/d in cage system, p>0.05) were same. However, quails housed on deep litter consumed more feed from 43-56 days of age (25.34±1.77g/d vs. 22.99±1.55g/d). Quails reared on deep litter also grew faster during the first week of that period (3.33±1.70g/d vs. 0.69±0.87g/d). However, gain in body weight was noticed from day 22 to day 49 but a sudden decline thereafter for all quails regardless of sex and housing system. Carcass yield was not affected by housing system but values for thighs, empty gizzard and liver of quails kept on deep litter were higher (respectively 12.95±0.86% vs. 11.99±0.83%, 2.12±0.18% vs. 1.84±0.20%, 2.11±0.59% vs. 1.88±0.43%; p<0.05). Production costs were the same (p>0.05) whether on deep litter (3414.30±172.95CFA/kg) or in cages (3283.43±77.72CFA/kg). However, the production cost per kilogram of carcass of male quails was lower compared to females (3205.88±138.95CFA/kg vs. 3484.35±131.57CFA/kg, respectively) regardless of the housing system. Sex and age of quails affect performance and not the type of housing system.